2020
DOI: 10.51372/bioagro331.3
|View full text |Cite
|
Sign up to set email alerts
|

Interferencia de Cenchrus echinatus y Rottboellia exaltata en el crecimiento del frijol caupí

Abstract: El frijol caupíes un cultivo importante para la seguridad alimentaria de la población mundial;sin embargo, su producción es afectada constantemente por la interferencia de las malezas. El objetivo de estainvestigación fue determinar el efecto de la interferenciadelasmalezasen diferentes densidades de competencia sobre las características de crecimiento del cultivo. El estudio fue conducido mediante diseño de bloques al azar en arreglofactorial 2x4 para análisis del cultiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…In addition, the negative correlation between the cover of C. echinatus and the measured diversity indices was significant. In this regard, it was reported that the interference effect of C. echinatus was higher as the density of this weed increased [32]. Germination may be delayed or completely inhibited due to the interspecific neighborhoods [33].…”
Section: Discussionmentioning
confidence: 93%
“…In addition, the negative correlation between the cover of C. echinatus and the measured diversity indices was significant. In this regard, it was reported that the interference effect of C. echinatus was higher as the density of this weed increased [32]. Germination may be delayed or completely inhibited due to the interspecific neighborhoods [33].…”
Section: Discussionmentioning
confidence: 93%
“…In addition, the negative correlation between the cover of C. echinatus and the measured diversity indices was significant. In this regard, it was reported that interference effect of C. echinatus was higher as the density of this weed increases [43]. Germination may be delayed or completely inhibited due to the interspecific neighborhoods [44].…”
Section: Germination (%)mentioning
confidence: 93%
“…: Pennisetum polystachion), Rottboellia exaltata, and Bothriochloa pertusa. Cenchrus polystachion [98] and Rottboellia exaltata, especially, are annuals, which are usually cut and carried during the early wet season before they start to flower and are fed to cattle in the pen, playing an important role in fodder composition in West Timor for fattening cattle, though in many places these two annuals are considered weeds [99][100][101][102][103]. Other grasses are usually free grazed or fed to the animals by tethering them in communal native pastures.…”
Section: Natural Vegetation Biodiversity In Relation To Livestock Far...mentioning
confidence: 99%